Adherence to recommendations for ART and targeted PrEP use among HIV serodiscordant couples in East Africa: the "PrEP as a bridge to ART" strategy - Nicholas Musinguzi; Lara Kidoguchi; Nelly R. Mugo; Kenneth Ngure; Elly Katabira; Connie L. Celum; Jared M. Baeten; Renee Heffron; Jessica E. Haberer; on behalf of the Partners Demonstration Project Team (BMC, 2020)
Abstract Background PrEP use should be aligned with periods of risk for HIV acquisition. For HIV serodiscordant couples, PrEP can be used as a bridge until the partner living with HIV takes antiretroviral therapy (ART) long enough to achieve viral suppression (the "PrEP as a Bridge to ART" strategy). However, adherence to this strategy is unknown. Methods In a demonstration project in Kenya and Uganda, HIV-uninfected partners of serodiscordant couples were advised to take PrEP until the partner living with HIV took ART for ≥ 6 months. PrEP discontinuation was then recommended unless there were concerns about ART adherence, immediate fertility intentions, or outside partners with unknown HIV/ART status. Electronic adherence monitoring and socio-behavioral questionnaire data were used in logistic regression models to explore completion of this strategy and continuation of PrEP beyond recommendations to stop its use. Results Among 833 serodiscordant couples, 436 (52%) HIV-uninfected partners completed ≥ 6 months of PrEP as a bridge to ART. Strategy completion was associated with older age (aOR per 5 years = 1.1; p = 0.008) and having fewer children (aOR = 0.9; p = 0.019). Of the 230 participants encouraged to stop PrEP according to strategy recommendations, 170 (74%) did so. PrEP continuation among the remaining 60 participants was associated with more education (aOR = 1.1; p = 0.029), a preference for PrEP over ART (aOR = 3.6; p = 0.026), comfort with managing their serodiscordant relationship (aOR = 0.6; p = 0.046), and believing PrEP makes sex safe (aOR = 0.5; p = 0.026). Conclusion Half of participants completed the PrEP as a bridge to ART strategy and the majority stopped PrEP as recommended. These findings suggest that targeting PrEP to periods of risk is a promising approach; however, tailoring counseling around aligning PrEP use and HIV risk will be important for optimal strategy implementation.